Consumer valuation of alternative meat origin labels - Tonsor, Glynn T.; Schroeder, Ted C.; Lusk, Jayson L. (My University, 2013)
Results from a split-sample survey of the U.S. population reveal consumers prefer meat products carrying origin information to unlabeled alternatives. Consumers are largely unaware of origin labeling laws and are indifferent to an important aspect of the implementation of current mandatory country of origin information rules in the U.S. In particular, consumers value meat products labeled “Product of North America” approximately the same as “Product of United States.” Despite the similarity of these two labels, they have vastly different implications in terms of trade and segregation costs. Our results suggest that a transition from one label to the other is equally satisfying for the consumer while being less costly for processors and more acceptable to trade partners.
Keywords: Consumer demand; Mandatory country of origin labeling; Meat; Meat labeling; Policy awareness; Split sample experiment; Willingness to pay